ENANTIOSELECTIVE ALKINYLATION OF BENZALDEHYDE AND ITS DERIVATIVES IN THE PARTICIPATION OF PHENYLACETYLENE (Scientific journal of the Fergana State University, 2023)
To date, the development of methods for synthesis of biologically active substances is based on the interaction of carbonyl, carboxyl and hydroxyl groups in the alkyne molecule with organic compounds. In this work, the reaction of enantioselective alkynylation of benzaldehyde and a number of its derivatives using phenylacetylene in the Zn(OTf)2/TBAF•3H2O/NEt3/MeCN catalytic system has been studied for the first time. In the synthesis of aromatic acetylenic alcohols, the effect of the nature and amount of solvents, catalysts, reagents, and substrates on the product yield is systematically analyzed. Based on the results obtained, the most alternative reaction conditions for the synthesis of aromatic acetylenic alcohols in the Zn(OTf)2/TBAF•3H2O/NEt3/MeCN complex catalytic system were determined.